Illocutionary Speech Acts Analysis in Nadhira Afifa's Speech as A Student Speaker at Harvard Graduation 2020 - Firda Amalia; Didin Nuruddin Hidayat; Alek Alek (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
The present study aims to find out the types of illocutionary act in Nadhira Afifa’s speech as a student’s speaker as Master of Public Health in Harvard Graduation 2020. The types of illocutionary which was promoted by Yule (1996) focused in this study. The study used qualitative descriptive by analyzing Nadhira’s speech as the main data. Furthermore, the sources of the data in this study was collected by downloading the video of speech from YouTube. Then, the data are analyzed and transcribed into the written form. Furthermore, the data were grouped into five types of illocutionary speech acts. The finding revealed that there are four typed of illocutionary speech acts which are used in Nadhira's speech. They were representative, expressive, directive and commissive. In this term, one of illocutionary acts type which is declarative did not find in the speech. Apparently, the preferable type of illocutionary speech act was representative. In this term, Nadhira delivered the information related to the importance of being part of public health during this day that she concerned about. Meanwhile, the percentage revealed the most and the least used of types of illocutionary speech acts by Nadhira's speech. They were representative (56.4%), expressive (30.7%), directive (5.1%), commissive (7.7%) and declarative (0%). It means that representative and expressive are being preferable. It is occurred because the context and the speaker who has the speech is a student’s speaker in graduation day. Keywords: illocutionary acts, speech act, speech, analysis Abstrak Penelitian ini ditujukan untuk mengetahui jenis-jenis ilokusi dalam Pidato Nadhira Afifa sebagai pembicara mahasiswa Magister Kesehatan Masyarakat di Harvard Graduation 2020. Jenis Jenis ilokusi yang dipromosikan oleh Yule (1996) difokuskan dalam penelitian ini. Penelitian ini menggunakan deskriptif kualitatif dengan menggunakan pidato Nadhira sebagai data utama. Selanjutnya sumber data dalam penelitian ini diunduh dari YouTube. Data tersebut dianalisa, ditranskripsikan ke dalam bentuk tertulis dan dikelompokkan menjadi lima jenis tidan tutur ilokusi. Hasil penelitian menunjukkan bahwa ada empat jenis tindak ilokusi yang digunakan dalam pidato Nadhira yaitu representatif, ekspresif, direktif dan komisif. Dalam hal ini, deklaratif tidak ditemukan dalam pidato tersebut. Representatif menjadi tindak tutur yang lebih disukai dalam pidato ini. Nadhira menyampaikan informasi terkait pentingnya menjadi bagian dari kesehatan masyarakat. Sementara itu, persentasi dalam tindak ilokusi ditunjukkan dengan representatif (56,4%), ekspresif (30,7%), direktif (5,1 %), komisif (7,7%) dan deklaratif (0%). Ini artinya representatif dan espresif lebih disukai. Hal ini terjadi karena konteks dan penuturnya adalah sebagai pembicara mahasiswa pada hari wisuda. Kata kunci: tindak ilokusi, tindak tutur, analisis